TANGGUNG JAWAB HUKUM PEMBERI KERJA ATAS KETERLAMBATAN PEMBAYARAN IURAN BPJS KETENAGAKERJAAN DALAM PERSPEKTIF UNDANG-UNDANG SISTEM JAMINAN SOSIAL NASIONAL - Erni Haryani; Dian Utari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Abstract Employment social security is a constitutional right of workers guaranteed under the National Social Security System (Sistem Jaminan Sosial Nasional/SJSN). However, delays in the payment of BPJS Ketenagakerjaan contributions by employers remain a recurring issue, potentially hindering workers’ rights to social protection. This study aims to analyze the legal provisions governing employers’ obligations to pay BPJS Ketenagakerjaan contributions under Law Number 40 of 2004 concerning the National Social Security System and to examine the legal responsibilities and sanctions imposed for late contribution payments. This research employs a normative legal method using statutory, conceptual, and analytical approaches. Data were collected through a literature review of primary, secondary, and tertiary legal materials and analyzed descriptively. The findings indicate that the payment of BPJS Ketenagakerjaan contributions is a mandatory legal obligation, including the registration of workers and the timely payment of contributions. Delayed payments do not eliminate the employer’s legal responsibility and may result in administrative, civil, and criminal sanctions as forms of legal protection to ensure the fulfillment of workers’ social security rights. Keywords: Legal Responsibility, Employer, BPJS Ketenagakerjaan, Late Contribution Payment, National Social Security System